Hajimete no jidō tesuto : Web shisutemu no tame no jidō tesuto kiso - Rasmusson, Jonathan (Orairī Japan, 2017)
"This book is for everyone who needs to test the web. Follow the testing pyramid and level up your skills in user interface testing, integration testing, and unit testing. If you're a software tester new to automated testing, you'll learn the basics and build confidence. If you're a developer, you'll find out how to move fast without breaking stuff, test RESTful web services and legacy systems, organize your tests, and understand mocking and test-driven development. And if you're a team lead, this is the Rosetta Stone you've been looking for to bridge that testing gap between your developers and your testers. Packed with cartoons, graphics, best practices, war stories, plenty of humor, and hands-on tutorial exercises. The Way of the Web Tester shows you how to do the right things, the right way"--